Toy Industry As A Mainstream Business Idea In Animation Industry - Mochamad Faizal Rochman (Institut Seni Indonesia Yogyakarta, 2022)
This article examines the aspects that influenced the emergence of the animation industry format aimed specifically at selling toys. In addition, this article also aims to find out whether the purpose of this animation business is still relevant to be used today by analyzing animated characters and their toy figures related to the exploration of culture, ideology, and supporting factors. In its first development, animation was used to deliver messages in the advertising industry. Then animation became a promising industry with the emergence of Snow White which was made for big-screen consumption. The emergence and popularity of television in the '60s provided new opportunities for the animation industry, stimulating the development of animated television series. Animated television series have a significant role in helping the marketing of derivative products in the animation industry. The 80s became a golden year for the animation industry and its derivatives, which was marked by the emergence of many animated films with the main business objective of selling toys. The declining popularity of television and the increasing use of the internet as a medium of entertainment will undoubtedly impact the development of the animation and toy industry. The power of character toy figures as a sole entertainment has also begun to come under pressure from the video game industry.